2016
DOI: 10.5194/jsss-5-283-2016
|View full text |Cite
|
Sign up to set email alerts
|

Hot-film and calorimetric thermal air flow sensors realized with printed board technology

Abstract: Abstract. This paper addresses the development of flow sensors optimized for heating, ventilating, and air conditioning systems. The sensors are based on the printed circuit board technology facilitating robust, flexible (in terms of layout), and cost-effective devices. Two approaches for measuring fluid quantities like flow velocity over the whole cross section are investigated in this context. The first one relies on hot-film transduction and stands out for its simplicity, but also shows some severe limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, the heat transfer coefficient h ∞ relates to the flow speed U ∞ by the laminar boundary layer theory, as in Equation (3) or Equation ( 4), subject to a flat plate under the medium value of the Reynolds number flow [182]. Substituting Equation (4) into Equations ( 1) and ( 2) can correlate the temperature difference and the flow speed.…”
Section: Flow Sensor Designmentioning
confidence: 99%
“…In addition, the heat transfer coefficient h ∞ relates to the flow speed U ∞ by the laminar boundary layer theory, as in Equation (3) or Equation ( 4), subject to a flat plate under the medium value of the Reynolds number flow [182]. Substituting Equation (4) into Equations ( 1) and ( 2) can correlate the temperature difference and the flow speed.…”
Section: Flow Sensor Designmentioning
confidence: 99%
“…In this case, temperature sensors arranged around the heater are needed for detection. Their temperature difference is a function of the flow velocity [9,10,11]. Time-of-flight (TOF) flow sensors measure the propagation of a heat pulse over a known distance between the heater and the temperature sensor located downstream of the heater [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, temperature sensors arranged around the heater are needed for detection. Their temperature difference is a function of the flow velocity [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MEMS hot-film air flow sensor has been widely used in the fields of aerospace, automotive, biomedical, environmental monitoring, semiconductor, and domestic appliances due to its ability of indirect measurement of air mass flow via measurements of temperature changes and the characteristics of high accuracy, fast response, and low power consumption [1][2][3]. However, in practical applications, it is found that if the gas to be measured contains aerosol particles, oil mist, etc., the surface of the sensor chip will be contaminated, which affects the accuracy of the sensor.…”
Section: Introductionmentioning
confidence: 99%